2015
DOI: 10.1002/brb3.342
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement desensitization and reprocessing (EMDR) therapy in the treatment of depression: a matched pairs study in an inpatient setting

Abstract: BackgroundDepression is a severe mental disorder that challenges mental health systems worldwide as the success rates of all established treatments are limited. Eye Movement Desensitization and Reprocessing (EMDR) therapy is a scientifically acknowledged psychotherapeutic treatment for PTSD. Given the recent research indicating that trauma and other adverse life experiences can be the basis of depression, the aim of this study was to determine the effectiveness of EMDR therapy with this disorder.MethodIn this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 35 publications
(33 reference statements)
1
32
0
3
Order By: Relevance
“…Moreover, due to a close physical distance between neurologic bonds, the therapeutic effect is observed in a short period of time . In the AIP model as a guide of the EMDR therapy, it is believed that stored memories can lead to mental disorders . EMDR stimulates the information processing system in the brain and reprocesses information .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, due to a close physical distance between neurologic bonds, the therapeutic effect is observed in a short period of time . In the AIP model as a guide of the EMDR therapy, it is believed that stored memories can lead to mental disorders . EMDR stimulates the information processing system in the brain and reprocesses information .…”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al stated that EMDR was an important treatment for the reduction of depression and anxiety. Behnammoghadam et al and Hase et al reported statistically significant reductions in the depressive symptoms of patients after the use of EMDR. Staring et al compared the effects of EMDR and competitive memory training (COMET), that were used in combination in patients with anxiety (n = 47).…”
Section: Introductionmentioning
confidence: 96%
“…Eye Movement Desensitization and Reprocessing (EMDR) therapy was introduced in 1987 as a treatment for post-traumatic stress disorder (PTSD). EMDR therapy is not only an evidence-based treatment of PTSD ( Bisson and Andrew, 2007 ; Watts et al, 2013 ; World Health Organization [WHO], 2013 ; Schulz et al, 2015 ), but is also a potentially effective treatment for various other mental disorders as affective disorders ( Landin-Romero et al, 2013 ; Hofmann et al, 2014 ; Novo et al, 2014 ; Hase et al, 2015 ), chronic pain ( Schneider et al, 2005 ; Wilensky, 2006 ; de Roos et al, 2010 ; Gerhardt et al, 2016 ), addiction ( Hase et al, 2008 ; Abel and O’Brien, 2010 ), or obsessive compulsive disorders ( Marsden et al, 2017 ). Functional imaging studies enable us to understand the working mechanisms of EMDR therapy to a great extent ( Pagani et al, 2012 ; Lee and Cuijpers, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…"Standardized CBT ‡ and EMDR § interventions can significantly improve functioning of disaster-exposed children" (de Roos, Greenwald, den Hollander-Gijsman, Noorthoorn, van Buuren, &de Jongh, 2011). "EMDR therapy shows promise as an effective treatment for depressive disorders" (Hase, Balmaceda, Hase, Lehnung, Tumani, Huchzermeier, &Hofmann, 2015). Cognitive Behavior Therapy was used with childhood traumatic grief (CTG) (Brown, Pearlman, & Goodman, 2004), and with depression (Oras, De Ezpeleta, &Ahmad, 2004;Cohen, 2005;Damra&Nassar, 2014).…”
Section: Introductionmentioning
confidence: 99%